A Comparative Study of Students Motivation in Learning English with Curriculum 2013 and Merdeka Curriculum - Yosafat Watem; Nurteteng; Agus Setiawan (TEKILA: Journal of Language Teaching and Literature, 2024)
This study investigates the impact of curriculum design on student motivation in learning English, comparing the Merdeka Curriculum and Curriculum 2013 at SMAN 4 Raja Ampat. A total of 80 students participated, with 40 first-grade students taught under the Merdeka Curriculum and 40 second-grade students taught under Curriculum 2013, selected through random sampling. Motivation levels were assessed using a 20-item Likert-scale questionnaire measuring intrinsic and extrinsic motivation. Data were analyzed using descriptive statistics and an independent samples t-test to determine significant differences between the two groups.The findings revealed that students in the Merdeka Curriculum group demonstrated significantly higher motivation levels (Mean = 4.20, SD = 0.40) compared to those in the Curriculum 2013 group (Mean = 3.80, SD = 0.50). A statistically significant difference was observed (t = 3.36, p = 0.001), highlighting the Merdeka Curriculum’s effectiveness in fostering student motivation through its flexibility and contextual relevance. Additionally, 62.5% of students in the Merdeka Curriculum group exhibited high motivation, compared to only 30% in the Curriculum 2013 group. These results underscore the importance of adopting student-centered and adaptive curricula, particularly in remote and diverse educational settings. The study recommends professional development for teachers to maximize the potential of flexible curricula and further research on their long-term academic impacts.